Analisis Kondisi Iklim dan Pemanfaatannya untuk Penetapan Musim Tanam dan Pola Tanam di Daerah Taniwel Kabupaten Seram Bagian Barat - Sitorus, Bangga; Laimeheriwa, Semuel; Madubun, Elia Leonard (Fakultas Pertanian, Universitas Pattimura, 2023)
A cropping pattern is an agricultural management activity that takes climate and soil conditions into account and seeks to achieve maximum results. Controlling cropping patterns is part of agricultural action planning to minimize the risk of crop failure. The purpose of this study is to (i) describe the climatic conditions in the Taniwell area, (ii) establish an effective growing season in the Taniwell area, and (iii) determine planting patterns for food crops in the Taniwell area. That's it. Length of growing season available. This study used his monthly climate data for 30 observation years from 1992 to 2021 from the Namlea Meteorological Station. Data analysis by following steps: (i) Analysis of rainfall (ii) Calculation of average rainfall (iii) Determination of rainfall with 75% probability (iv) Determination of planting season and planting pattern. The results showed that the effective growing season in the Taniwell area lasted 6 months and 24 days. It starts on December 1st and ends on June 24th.